The Political Economy of Deforestation in Papua: Hegemony, Land Dispossession, and the Global Frontiers of Resource Extraction - Inez Cara Alexander Phoek; Hendrik Susanto; Simon Ebel Maris Phoek; Eka Setiawati; Lavenia Lauwinata (Journal of Economics and Management, 2026)
This study explores the political economy of deforestation in Papua, Indonesia, by assessing how state development strategies, transnational capital growth, and indigenous land governance interact within a fragile frontier ecosystem. Applying a qualitative method with a critical case study design, the research centers on Merauke Regency, especially areas influenced by large-scale agribusiness and food estate projects. Data were obtained through document review, semi-structured interviews, and field observations, then examined through thematic coding and analytic narrative guided by political ecology, neo-Gramscian international political economy (Cox, 1981; Gill, 1993), structural power theory (Strange, 1988), accumulation by dispossession, and global commodity chain perspectives. The findings show that deforestation in Papua results from the alignment of state-driven development programs, transnational capital interests, and global commodity networks operating through concession-based land governance that often weakens indigenous customary rights. The study also finds that plasma plantation schemes and corporate social responsibility (CSR) programs can serve as institutional tools to lessen socio-ecological inequality. However, their application remains inconsistent across local settings. Furthermore, agribusiness expansion and related infrastructure development have produced complex impacts, including environmental damage, social displacement, declining indigenous livelihoods, and stronger disputes over land and territorial claims. This study contributes to political ecology and critical international political economy by framing Papua as a geopolitical frontier where capitalist accumulation, state territorial control, and indigenous resistance shape contemporary forest governance.